2021
DOI: 10.2807/1560-7917.es.2021.26.43.2100830
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 antibodies 6 months into the vaccination campaign in Geneva, Switzerland, 1 June to 7 July 2021

Abstract: Background Up-to-date seroprevalence estimates are critical to describe the SARS-CoV-2 immune landscape and to guide public health decisions. Aim We estimate seroprevalence of anti-SARS-CoV-2 antibodies 15 months into the COVID-19 pandemic and 6 months into the vaccination campaign. Methods We conducted a population-based cross-sectional serosurvey between 1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 25 publications
8
58
3
Order By: Relevance
“…SalivaHIS results were compared with other national and international seroprevalence studies that were conducted during the same study period. From these studies it appears that the seroprevalence was 66.1% in the general population in Geneva (July 2021) [ 8 ], 89.4% in the general population in England (July 2021) [ 11 ], 75.9% among blood donors in Austria (July 2021) [ 10 ], and 98.0% (July 2021) among Belgian blood donors [ 12 ]. The seroprevalence of 78.1% (July 2021) observed in our study is, thus, relatively consistent with what was found in those other studies [ 8 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SalivaHIS results were compared with other national and international seroprevalence studies that were conducted during the same study period. From these studies it appears that the seroprevalence was 66.1% in the general population in Geneva (July 2021) [ 8 ], 89.4% in the general population in England (July 2021) [ 11 ], 75.9% among blood donors in Austria (July 2021) [ 10 ], and 98.0% (July 2021) among Belgian blood donors [ 12 ]. The seroprevalence of 78.1% (July 2021) observed in our study is, thus, relatively consistent with what was found in those other studies [ 8 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…From these studies it appears that the seroprevalence was 66.1% in the general population in Geneva (July 2021) [ 8 ], 89.4% in the general population in England (July 2021) [ 11 ], 75.9% among blood donors in Austria (July 2021) [ 10 ], and 98.0% (July 2021) among Belgian blood donors [ 12 ]. The seroprevalence of 78.1% (July 2021) observed in our study is, thus, relatively consistent with what was found in those other studies [ 8 , 10 , 11 , 12 ]. Of course, these results should be interpreted with caution as the epidemiological situation and the vaccination campaign were different in each country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In June/July 2021, we conducted a survey selecting a representative sample of children and adolescents of a Swiss canton population (Ethics Committee ID: 2020-0088) [6]. Parents of school-aged children reported information about them missing school because of COVID-19, from August 2020 to June 2021.…”
Section: Methodsmentioning
confidence: 99%
“…These studies show that SARS-CoV-2 infections in children have been frequently underdiagnosed. 12 , 13 , 14 Many of these studies conducted in different countries before 15 , 16 , 17 , 18 and after vaccine availability 19 showed a lower number of infection-derived SARS-CoV-2 antibody detection in children compared to adults. However, country and regional study differences conducted at varying timepoints during the pandemic have reported mixed results.…”
Section: Introductionmentioning
confidence: 99%